Digital transformation strategy: a systematic literature review / Siti Noorsiah Jamaludin and Abd Samad Hasan Basari - Jamaludin, Siti Noorsiah; Basari, Abd Samad Hasan (Universiti Teknologi MARA, 2022)
Digital transformation strategy has been an issue highlighted by many researchers and has become a topic of importance to be discussed. The purpose of this paper is to present the results of a review of 20 selected studies which include 14 different frameworks and models of different digital transformation strategies. The main focus of the study is on the frameworks and models in measuring digital transformation strategies. The findings indicate the measurements applied in digital transformation strategies vary between industries and organisations. The findings reveal that most existing frameworks and models provide incomplete illustrations of digital transformation strategies that very little research discussed on frameworks or models to measure digital transformation strategies. Thus, it is evident that research about digital transformation strategies needs more attention by researchers to explore in the future.